2022
DOI: 10.1097/apo.0000000000000545
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Gene Manipulation Strategies for the Treatment of Monogenic Eye Disease

Abstract: Genetic eye diseases, representing a wide spectrum of simple and complex conditions, are one of the leading causes of visual loss in children and working adults, and progress in the field has led to changes in disease investigation, diagnosis, and management. The past 15 years have seen the emergence of novel therapies for these previously untreatable conditions to the extent that we now have a licensed therapy for one form of genetic eye disease and many more in clinical trial. This is a systematic review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…The SDF-1/CXCR4 signal axis induced BMSCs to migrate to the wound site and secrete various growth factors, such as vascular endothelial growth factor, fibroblast growth factor, and transforming growth factor β, forming many vascular networks and participating in wound repair 27. Previous studies reported that hematopoietic stem cells expressing CXCR4 could migrate with chemotactic processes along the concentration gradient of SDF-1 32,33. BMSC was also reported to express CXCR4, and it was assumed that the migration mechanism of BMSC may have similar characteristics to hematopoietic stem cells 34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDF-1/CXCR4 signal axis induced BMSCs to migrate to the wound site and secrete various growth factors, such as vascular endothelial growth factor, fibroblast growth factor, and transforming growth factor β, forming many vascular networks and participating in wound repair 27. Previous studies reported that hematopoietic stem cells expressing CXCR4 could migrate with chemotactic processes along the concentration gradient of SDF-1 32,33. BMSC was also reported to express CXCR4, and it was assumed that the migration mechanism of BMSC may have similar characteristics to hematopoietic stem cells 34…”
Section: Discussionmentioning
confidence: 99%
“…27 Previous studies reported that hematopoietic stem cells expressing CXCR4 could migrate with chemotactic processes along the concentration gradient of SDF-1. 32,33 BMSC was also reported to express CXCR4, and it was assumed that the migration mechanism of BMSC may have similar characteristics to hematopoietic stem cells. 34 The Molecular Mechanism of SDF-1 Inducing BMSC Migration…”
Section: Sdf-1mentioning
confidence: 99%
“…Gene manipulation, new approaches using epigenetics and degenerative retinal diseases, and retinal organoids in treating retinal diseases are not covered in this special issue but have good potential applications in the future. [9][10][11][12][13]…”
mentioning
confidence: 99%
“…The clinical trials currently registered for monogenic eye diseases are summarized by Burgess et al in their article in this issue. The 60 trials described show not only the speed with which research findings are being translated into clinical reality but also the hope that many patients may soon have treatments available 5. The most successful gene therapy for RP so far has been the subretinal application of voretigene neparvovec-rzyl (Luxturna) for the treatment of the RPE65 mutation-associated type of retinal dystrophy 6.…”
mentioning
confidence: 99%
“…The 60 trials described show not only the speed with which research findings are being translated into clinical reality but also the hope that many patients may soon have treatments available. 5 The most successful gene therapy for RP so far has been the subretinal application of voretigene neparvovec-rzyl (Luxturna) for the treatment of the RPE65 mutation-associated type of retinal dystrophy. 6 This therapy improves vision and follow-up data so far have shown an effect lasting for at least 4 years.…”
mentioning
confidence: 99%